(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Palm oil mill effluent (POME) is a wastewater generated from palm oil milling activities which requires effective treatment before being discharged into the watercourses due to its highly polluting properties. Hence this study was aimed at evaluating the biosurfactant-producing microorganisms from POME at different depths from large and small/medium scale enterprises in Edo State, Nigeria. POME was aseptically collected using sterile bottles from various depths: top, middle and bottom in selected palm oil companies across Edo State, Nigeria. The companies were categorized into large-scale enterprises (L.S.E.), which included Okomu Oil Palm and NIFOR and small and medium-scale enterprises (S.M.E.), comprising Ovbiogie, Sapele Road and Aduwawa oil palm companies. The bacteria isolated were Bacillus cereus, Pseudomonas aeruginosa, Bacillus amyloliqefaciens, Klebsiella aerogenes and Escherichia coli. Fungi like Aspergillus niger, Fusarium solani, Penicillium chrysogenum, Microsporum sp., Penicillium citrinum and Aspergillus flavus were also isolated from these samples using the Pour plate techniques. The bacterial species obtained in the pure culture of substrate were identified using standard bacterial and fungal techniques. Isolated organisms were screened for their ability to produce biosurfactants using oil spreading assay, hemolytic, and emulsification activity. The test of how susceptible the isolates were to antibiotics was conducted with the aid of the Kirby-Bauer disk diffusion assay. The data obtained were analyzed using Microsoft Excel 2019 and PhyloT software to establish the relationship between isolated microorganisms from POME. The results of the total heterotrophic bacterial counts ranged from log10 3.90±1.00 cfu/g (Small and Medium Scale- Sapele Road) to log10 4.66±3.0 cfu/g (Large Scale Enterprise- Okomu). The total fungal counts ranged from log10 3.78±1.00 cfu/g (Small and Medium Scale- Aduwawa) to log10 4.34±2.00 cfu/g (Small and Medium Scale- Aduwawa). The difference in percentage reduction in the density of microbes between the top and bottom depth ranged from 43.18% (NIFOR) to 72.29 % (Okomu). Also, a significant difference (p<0.05) between the microbial diversity of large-scale and small-scale oil-producing enterprises was observed. The isolated bacteria included Bacillus cereus, Pseudomonas aeruginosa, Bacillus amyloliqefaciens, Klebsiella aerogenes and Escherichia coli. The isolated fungi were Aspergillus niger, Penicillium citrinum, Penicillium chrysogenum, Aspergillus flavus, Microsporum sp. and Fusarium solani. Biosurfactant screening results revealed that most microbial isolates were potential biosurfactant producers, with Bacillus sp. showing the highest clear zone of oil spread assay. However, specific isolates like E. coli and Microsporum sp. did not produce any clear zone for oil spread assay. More so, Bacillus sp. was found to be the best biosurfactant producer due to its hemolytic activity and the assay with the highest zone (10mm) of displacement. POME is home to many microorganisms of importance to both industrial and environmental processes. This research has demonstrated that POME serves as a reservoir for microorganisms capable of producing biosurfactants.